Sodium ion positive electrode material containing sodium vacancy on surface layer, preparation method and sodium secondary battery

By creating sodium vacancy on the surface of the sodium ion O3-type layered oxide positive electrode material, the problems of slow Na+ diffusion kinetics and poor air stability are solved, and the electrochemical performance and air stability are significantly improved, and the circulation performance of sodium secondary batteries is improved.

CN119695135AActive Publication Date: 2025-03-25YIBIN LIBODE NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411847698.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The sodium ion O3-type layered oxide cathode material has poor electrochemical performance due to the slow diffusion kinetics of Na+ and poor air stability.

Method used

By creating sodium vacancy on the O3 layered oxide surface, electrochemical performance is optimized, air stability is improved, surface residual alkali is reduced, and material processing performance is improved. The specific method includes dispersing the O3-type layered oxide powder in a solution containing an organic cationic compound, heating and stirring, filtering, drying and sintering to create a sodium vacancy.

Benefits of technology

The electrochemical performance of O3 layered oxide positive electrode material is significantly improved, the residual alkali on the surface is reduced, the air stability and processing performance are improved, and the circulation performance of sodium secondary batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695135A_ABST
    Figure CN119695135A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion positive electrode material with a surface layer containing a sodium vacancy, a preparation method and a sodium secondary battery. The sodium ion positive electrode material containing the sodium vacancy on the surface layer is an O3 type layered oxide positive electrode material containing the sodium vacancy on the surface layer, the O3 type layered oxide positive electrode material comprises a doping element, and the valence of the doping element in a sodium ion layered oxide is one or more of + 1, + 2, + 3, + 4, + 5 and + 6. The O3 type layered oxide positive electrode material is dispersed in the solution containing the organic cation compound, and the organic cation is removed through ion exchange and high-temperature sintering to create sodium vacancy, so that the electrochemical performance optimization of the O3 type layered oxide positive electrode material is realized, the air stability is improved, the surface residual alkali is reduced, and the processing performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium electric materials, and in particular to a sodium ion positive electrode material containing sodium vacancies on the surface, a preparation method thereof, and a sodium secondary battery. Background Art

[0002] Sodium ion O3-type layered oxide cathode materials are currently regarded as ideal supplementary substitutes for lithium battery ternary cathode materials due to their high theoretical specific capacity and process route close to lithium battery ternary cathode materials. + Radius ratio Li + The radius is large, and Na + In the O3-type layered oxide crystal structure, diffusion from one octahedral site to another requires passing through a tetrahedral interstitial site, which leads to inherently slow ion diffusion kinetics. In addition, Na + Comparison + It is more likely to react with H2O in the air and has poor air stability, which is not conducive to homogenization and the performance of electrochemical performance. Summary of the invention

[0003] The purpose of the present invention is to overcome the defects of the above technical background and provide a sodium ion positive electrode material with sodium vacancies on the surface, a preparation method and a sodium secondary battery.

[0004] The present invention optimizes electrochemical performance, improves air stability, reduces surface residual alkali, and improves material processing performance by creating sodium vacancies on the surface of O3 layered oxide.

[0005] The present invention solves the technical problem by adopting the following technical solutions.

[0006] The present invention provides a sodium ion positive electrode material containing sodium vacancies on the surface. The sodium ion positive electrode material containing sodium vacancies on the surface is an O3 type layered oxide positive electrode material containing sodium vacancies on the surface. The O3 type layered oxide positive electrode material includes a doping element. The valence of the doping element in the sodium ion layered oxide includes one or more of +1, +2, +3, +4, +5, and +6.

[0007] In some embodiments, the O3-type layered oxide positive electrode material comprises flaky and / or blocky single crystals with a particle size D50 of 3 μm-10 μm, and the sodium vacancies on the surface of the O3-type layered oxide positive electrode material account for 5%-15% of the total sodium content of the O3-type layered oxide.

[0008] In some embodiments, the chemical formula of the O3-type layered oxide includes Na x M y A zO2, wherein 0.7≤x≤1.0, 0<y<1, 0<z<1, M includes at least one element selected from Ni, Fe, Mn, Cu, Zn, and Ti, and the doping element A includes at least one element selected from K, Ca, Mg, Co, Ti, Al, Zr, Ce, Nb, Mo, Sr, Y, Sn, Sb, and W.

[0009] In some embodiments, a sodium ion positive electrode material slurry with a solid content of 60% and containing sodium vacancies on the surface can still flow normally without gelling after being placed in a 25% humidity environment for 24 hours; the surface residual alkali NaOH content of the sodium ion positive electrode material containing sodium vacancies on the surface is 500ppm-1000ppm, and the surface residual alkali NaOH content is 600ppm-1100ppm after being placed in the air for 10 days.

[0010] In some embodiments, the O3-type layered oxide containing sodium vacancies on the surface has a capacity of greater than 135 mAh / g at 0.1C in a 2-4.0V button half-cell at room temperature, a first efficiency greater than 95%, and a 50-cycle cycle retention rate greater than 95%.

[0011] The present invention also provides a method for preparing the above-mentioned sodium ion positive electrode material containing sodium vacancies on the surface, comprising: dispersing O3 type layered oxide powder in a solution containing an organic cationic compound, stirring under heating conditions, and then filtering, drying and sintering to obtain the sodium ion positive electrode material containing sodium vacancies on the surface.

[0012] In some embodiments, the preparation method of O3-type layered oxide powder includes a solid phase method and a precursor method, wherein: the solid phase method includes the following steps: after the Na source, M source and A source are uniformly mixed according to a set ratio, sintering at 950°C~1050°C in an air atmosphere for 10h~12h; the precursor method includes the following steps: after the M(OH)2 precursor, Na source and A source are uniformly mixed, sintering at 950°C~1050°C in an air atmosphere for 10h~12h, the Na source includes at least one of sodium carbonate or sodium hydroxide, the M source includes at least one of the oxide, carbonate, and hydroxide of the M element, and the A source includes at least one of the oxide, carbonate, phosphate, and hydroxide of the A element.

[0013] In some embodiments, the solution containing the organic cationic compound is obtained by dissolving the organic cationic compound in a solvent, wherein: the organic cationic compound includes one or more of a quaternary ammonium salt and a quaternary phosphonium salt, the quaternary ammonium salt has a general formula of R4NX, the four R groups are independently selected from C1-C4 alkyl groups, and X is Cl - Br - ,I - Any one of the quaternary phosphonium salts, the general formula of which is R4PX, the four R groups are independently selected from C1-C4 alkyl groups, and X is Cl -Br - ,I - Any one of the above, wherein the solvent includes one or more of deionized water, methanol, ethanol, and propanol.

[0014] In some embodiments, the dispersion temperature is 25°C-75°C, the drying temperature is 50°C-100°C, the drying time is 4h-8h, the sintering temperature is 600°C-800°C, and the sintering time is 6h-8h.

[0015] The present invention also provides a sodium secondary battery, which comprises the above-mentioned sodium ion positive electrode material with sodium vacancies on the surface or the sodium ion positive electrode material with sodium vacancies on the surface prepared by the above-mentioned preparation method.

[0016] The present invention has the following beneficial effects.

[0017] The present invention provides a sodium ion positive electrode material with sodium vacancies on the surface, a preparation method and a sodium secondary battery. The electrochemical performance of the O3 layered oxide positive electrode material provided by the present invention is significantly improved, the residual alkali on the surface of the O3 layered oxide positive electrode material is significantly reduced, and the residual alkali does not increase significantly when the material is placed in the air for a long time, and the O3 layered oxide positive electrode material has excellent processing performance, and the viscosity is small after being placed for 24 hours after homogenization, and it can still be coated normally. The sodium secondary battery prepared by using the sodium ion positive electrode material with sodium vacancies on the surface provided by the present invention has good electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 is the XRD pattern of the O3-type layered oxide (which may be referred to as the base sample) prepared in Comparative Example 1; Figure 2 is a SEM image of the O3-type layered oxide (which may be referred to as a base sample) prepared in Comparative Example 1; Figure 3 It is a comparison diagram of charge and discharge curves of a battery assembled using the O3 type layered oxide containing sodium vacancies on the surface prepared in Example 5 (which may be referred to as an improved sample) and the O3 type layered oxide prepared in Comparative Example 1 (which may be referred to as a basic sample); Figure 4 Comparison of cycle retention rates of batteries assembled using the O3-type layered oxide containing sodium vacancies on the surface prepared in Example 5 (which may be referred to as an improved sample) and the O3-type layered oxide prepared in Comparative Example 1 (which may be referred to as a basic sample); Figure 5 This is a comparison chart of the viscosity changes of the O3 type layered oxide containing sodium vacancies on the surface prepared by Example 5 (which can be called the improved sample) and the O3 type layered oxide prepared by Comparative Example 1 (which can be called the basic sample) exposed to air for 24 hours. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Otherwise, follow the normal conditions or the conditions recommended by the manufacturer. Manufacturers are all conventional products that can be purchased on the market.

[0021] The following is a detailed description of a sodium ion positive electrode material having sodium vacancies on the surface, a preparation method, and a sodium secondary battery provided in an embodiment of the present invention.

[0022] In a first aspect, an embodiment of the present invention provides a sodium ion positive electrode material having sodium vacancies on the surface. The sodium ion positive electrode material having sodium vacancies on the surface is an O3 type layered oxide positive electrode material having sodium vacancies on the surface. The O3 type layered oxide positive electrode material includes a doping element, and the valence of the doping element in the sodium ion layered oxide includes one or more of +1, +2, +3, +4, +5, and +6.

[0023] Sodium vacancy defects in the lattice can expand the interlayer spacing of transition metals, which is beneficial to Na + Diffusion kinetics. In addition, sodium vacancies can increase the average valence state of transition metals, further promote their oxidation resistance, and avoid spontaneous Na removal of O3-type layered oxides in the air. Therefore, the solution provided in the embodiment of the present invention aims to optimize electrochemical performance, improve air stability, reduce surface residual alkali, and improve material processing performance by creating sodium vacancies on the surface of O3 layered oxide positive electrode materials.

[0024] In some optional embodiments, the O3-type layered oxide containing sodium vacancies on the surface comprises flaky and / or blocky single crystals with a particle size D50 of 3 μm-10 μm, and the sodium vacancies on the surface of the O3-type layered oxide positive electrode material account for 5%-15% of the total sodium content of the O3-type layered oxide.

[0025] In some optional embodiments, the chemical formula of the O3-type layered oxide includes Na x M y A zO2, wherein 0.7≤x≤1.0, 0<y<1, 0<z<1, M includes at least one element selected from Ni, Fe, Mn, Cu, Zn, and Ti, and the doping element A includes at least one element selected from K, Ca, Mg, Co, Ti, Al, Zr, Ce, Nb, Mo, Sr, Y, Sn, Sb, and W.

[0026] The chemical formula of the O3-type layered oxide provided in the embodiment of the present invention includes Na x M y A z O2, in O3-type layered oxide Na x M y Doping element A in O2 can change the O3-type layered oxide Na x M y The crystal structure of O2 increases the distance between the Na layers, which is beneficial for the subsequent preparation of O3-type layered oxides with sodium vacancies on the surface. x M y Na in O2 + Ion exchange occurs with organic cations, thereby forming an O3-type layered oxide Na x M y The surface of O2 creates a suitable number of sodium vacancies, which is conducive to the deintercalation of sodium ions at the positive electrode material end.

[0027] In some optional embodiments, a sodium ion positive electrode material slurry with a solid content of 60% and containing sodium vacancies on the surface can still flow normally without gelling after being placed in a 25% humidity environment for 24 hours; the surface residual alkali NaOH content of the sodium ion positive electrode material containing sodium vacancies on the surface is 500ppm-1000ppm, and the surface residual alkali NaOH content is 600ppm-1100ppm after being placed in the air for 10 days.

[0028] In some optional embodiments, the O3-type layered oxide containing sodium vacancies on the surface has a capacity of greater than 135 mAh / g at 0.1C in a 2-4.0V button half-cell at room temperature, an initial efficiency greater than 95%, and a 50-cycle cycle retention rate greater than 95%.

[0029] The embodiment of the present invention provides a sodium ion positive electrode material containing sodium vacancies on the surface. The sodium vacancies on the surface of the sodium ion positive electrode material constitute a three-dimensional channel for Na ion transmission, thereby effectively promoting the insertion and removal of Na ions during the charge and discharge process. At the same time, the doping elements A in various valence states improve the interlayer spacing of the sodium ion positive electrode material. In addition, the doping elements in various valence states can improve the stability of the sodium ion positive electrode material, further improve the Na ion insertion and removal efficiency, and can inhibit the phase transition process with poor reversibility during the charge and discharge process. Therefore, the sodium ion positive electrode material provided by the embodiment of the present invention can improve the cycle performance of the sodium ion battery.

[0030] In a second aspect, an embodiment of the present invention also provides a method for preparing the above-mentioned sodium ion positive electrode material containing sodium vacancies on the surface, comprising: dispersing O3 type layered oxide powder in a solution containing an organic cationic compound, stirring under heating conditions, and then filtering, drying and sintering to obtain the sodium ion positive electrode material containing sodium vacancies on the surface.

[0031] At present, organic solution is usually used to clean and remove residual alkali on the surface of sodium ion layered oxide positive electrode materials. Although it will cause surface sodium vacancies to a certain extent, the effect is not good and the amount of organic solvent used is large, and the cost is high. After long-term practice, the inventor provides a preparation method of sodium ion positive electrode materials with sodium vacancies on the surface, which comprises: dispersing O3 type layered oxide positive electrode material powder in a solution containing an organic cationic compound, under stirring, the organic cations in the organic cationic compound and the Na in the O3 type layered oxide positive electrode material + Ion exchange occurs, and finally, organic cations are removed by high-temperature sintering to create sodium vacancies. The embodiment of the present invention provides the above-mentioned solution, which can simply and effectively create sodium vacancies on the surface of O3-type layered oxide positive electrode materials, improve the electrochemical properties of O3-type layered oxide positive electrode materials, and to a certain extent solve the problem of poor air stability of sodium-type layered oxide positive electrode materials.

[0032] In some optional embodiments, the preparation method of O3 type layered oxide powder includes a solid phase method and a precursor method, wherein: the solid phase method includes the following steps: after the Na source, M source and A source are uniformly mixed according to a set ratio, sintering at 950℃~1050℃ in an air atmosphere for 10h~12h; the precursor method includes the following steps: after the M(OH)2 precursor, Na source and A source are uniformly mixed, sintering at 950℃~1050℃ in an air atmosphere for 10h~12h, the Na source includes at least one of sodium carbonate or sodium hydroxide, the M source includes at least one of the oxide, carbonate, hydroxide of the M element, and the A source includes at least one of the oxide, carbonate, phosphate, hydroxide of the A element.

[0033] In some optional embodiments, the solution containing the organic cationic compound is obtained by dissolving the organic cationic compound in a solvent, wherein: the organic cationic compound includes one or more of a quaternary ammonium salt and a quaternary phosphonium salt, the quaternary ammonium salt has a general formula of R4NX, the four R groups are independently selected from C1-C4 alkyl groups, and X is Cl - Br - ,I - any one of the quaternary ammonium salts, such as tetramethylammonium chloride, tetrabutylammonium chloride, tetrabutylammonium bromide, the quaternary phosphonium salt has the general formula of R4PX, the four R groups are independently selected from C1-C4 alkyl groups, X is Cl- Br - ,I - The quaternary phosphonium salt comprises at least one of tetramethylphosphonium chloride, tetrabutylphosphonium chloride and tetrabutylphosphonium bromide. The solvent comprises one or more of deionized water, methanol, ethanol and propanol.

[0034] In some optional embodiments, the dispersion temperature is 25°C-75°C, the drying temperature is 50°C-100°C, the drying time is 4h-8h, the sintering temperature is 600°C-800°C, and the sintering time is 6h-8h.

[0035] In a third aspect, an embodiment of the present invention further provides a sodium secondary battery, which includes the above-mentioned sodium ion positive electrode material with sodium vacancies on the surface or the sodium ion positive electrode material with sodium vacancies on the surface prepared by the above-mentioned preparation method.

[0036] The present invention will be further described below in conjunction with the embodiments.

[0037] Examples 1-7 Preparation of O3-type layered oxide cathode material Na by precursor method 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (0.89 is the molar ratio of the measured Na element to Ni, Fe and Mn metal elements, hereinafter referred to as the sodium metal ratio), comprising the following steps: weigh 1 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 precursor, 0.47mol Na2CO3 were placed in a high-speed mixer and mixed at 500r / min-10min, 1000r / min-20min, and then the mixture was placed in a corundum crucible, heated to 1020℃ (air atmosphere) at a heating rate of 2℃ / min in a high-temperature box furnace, and kept warm for 12h. After naturally cooling to room temperature, the positive electrode material was taken out and crushed with a crusher, and then sieved with a 400-mesh screen to obtain O3-type layered oxide positive electrode material Na 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2.

[0038] Preparation of Na with sodium vacancies on the surface x(0.6<x<0.9) Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, according to the feed materials and proportions in Table 1. The steps are as follows: crush and sieve 0.5 mol Na 0.89 Ni 1 / 3 Fe 1 / 3 Mn1 / 3 O2 and C4H 12 ClN (tetramethylammonium chloride) is mixed according to a certain molar ratio, dispersed in 100 ml of deionized water, stirred in a water bath at a certain temperature to form a uniform slurry, slowly and continuously stirred for a certain period of time, and then the obtained slurry is filter-filtered using a positive pressure filter, and the obtained filter press material is dried in a drying oven at a temperature of 80°C for 3 hours. Finally, the obtained dry material is heated to 600°C in a muffle furnace at a heating rate of 3°C / min, and sintered for 8 hours to obtain an O3-type layered oxide positive electrode material containing sodium vacancies on the surface.

[0039] Embodiment 8-13 The overall steps for preparing the O3-type layered oxide positive electrode material in Examples 8-13 are similar to those for preparing the Na x(0.6<x<0.9) Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is similar, the difference is that when preparing O3 type layered oxide positive electrode materials, 1% mol K2CO3, 2% mol ZnO, 2% mol Co(OH)2, 2% mol TiO2, 1% mol Nb2O5, and 2% mol WO3 are added to the mixing process, and finally Na doped with elements of different valence states is obtained. x(0.6<x<0.9) A Z Ni (1-Z) / 3 Fe (1-Z) / 3 Mn (1-Z) / 3 O2.

[0040] The O3-type layered oxide positive electrode material doped with elements of different valence states and containing sodium vacancies on the surface was prepared according to the materials and proportions in Table 1. The steps were the same as those in Example 1-7.

[0041] Embodiment 14 Preparation of O3-type layered oxide cathode material Na by solid phase method 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, comprising the following steps: weighing 0.47mol Na2CO3, 0.33mol NiO, 0.33mol Fe2O3, and 0.33mol MnO2 respectively, placing them in a high-speed mixer and mixing them evenly at a standard of 500r / min-10min, 1000r / min-20min, and 500r / min-5min, then placing the mixture in a corundum crucible, heating it to 1050°C at a heating rate of 2°C / min in a high-temperature box furnace, and keeping it warm for 12h, after naturally cooling to room temperature, taking out the positive electrode material, crushing it with a crusher, and then sieving it with a 400-mesh screen to obtain an O3-type layered oxide positive electrode material Na 0.89 Ni 1 / 3Fe 1 / 3 Mn 1 / 3 O2.

[0042] Preparation of O3-type layered oxide cathode materials containing sodium vacancies on the surface x(0.6<x<0.9) Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, according to the feed materials and proportions in Table 1. The steps are the same as in Example 1-7.

[0043] Examples 15-19 Preparation of different organic cation salts as ion exchangers to obtain O3-type layered oxide cathode materials containing sodium vacancies on the surface x(0.6<x<0.9) Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, according to the feed materials and proportions in Table 1. The steps are the same as in Example 1-7.

[0044] Comparative Example 1 Na prepared by precursor method 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is used as O3 type layered oxide positive electrode material without any treatment.

[0045] Comparative Example 2 The O3 layered oxide powder Na prepared by the precursor method 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is directly washed with deionized water. The temperature during the washing process is 25°C and the stirring time is 0.5h.

[0046] Comparative Example 3 The O3 layered oxide powder Na prepared by the precursor method 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 is directly washed with ethanol. During the washing process, the temperature is 25°C and the stirring time is 0.5h.

[0047] Comparative Example 4 The steps are the same as those in Example 2, except that the positive electrode material used is 1 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and 0.375 mol Na2CO3 were prepared according to 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3O2 conditions are obtained.

[0048] Comparative Example 5 The steps are the same as those in Example 2, except that the positive electrode material used is 1 mol Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH)2 and 0.4 mol Na2CO3 were prepared according to 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 conditions are obtained.

[0049] Comparative Example 6 Same as Example 2, except that the dispersion temperature is 5°C.

[0050] Comparative Example 7 The same as Example 2, except that the stirring time is 2 min.

[0051] Comparative Example 8 The same as Example 2, except that the material obtained by stirring is not subjected to secondary sintering at 600°C.

[0052] The following Table 1 shows the process parameters of the materials obtained in Examples 1-19 and Comparative Examples 1-8 during the preparation process.

[0053] Table 1

[0054] Sodium ion battery assembly example The positive electrode materials obtained in Examples 1-19 and Comparative Examples 1-8 were prepared into sodium ion batteries according to the following steps, specifically as follows: 1. Put Na x(0.6<x<0.9) Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, polyvinylidene fluoride (PVDF), and acetylene black are mixed in a mass ratio of 90:5:5 and stirred evenly, and then a certain amount of nitrogen methyl pyrrolidone (NMP) is added and stirred continuously. After the mixture becomes a uniform slurry, it is evenly coated on the aluminum foil.

[0055] 2. Place the coated aluminum foil in a vacuum oven and dry it at 110°C, then roll it through a double-roller machine to make it flat and uniform, and finally dry it in a vacuum oven at 120°C for 12 hours.

[0056] 3. Punch the dried aluminum foil into sheets, weigh them, and assemble the battery in a glove box. The electrolyte used is composed of DMC (dimethyl carbonate) + EC (ethylene carbonate) solvent containing 1M NaPF6 sodium source. The electrode sheet and the sodium sheet are used as the positive electrode and the negative electrode respectively, and are assembled into a button-type half-cell in a glove box.

[0057] Test Results Figure 1 Na prepared by the precursor method 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The XRD diagram of O2 shows that its structure is R m space group, good crystallinity, and a small amount of NiO impurity peaks appear. Figure 2 for Na 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 The SEM image of O2 shows that its morphology is a single crystal in the form of flakes or blocks, with a size between 3μm and 10μm. 0.89 Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 (which can be called the basic sample) and Examples 2-22 prepared according to the feed materials and proportions in Table 1, and Na with sodium vacancies on the surface shown in Comparative Examples 1-5 x(0.6<x<0.9) Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 for electrochemical performance testing, such as Figure 3 As shown in the preferred embodiment 5, which can be referred to as an improved sample, by properly adjusting the sodium vacancies on the surface of the O3-type layered oxide material, the first charge and discharge efficiency can be significantly improved while less affecting the capacity, and the cycle stability can be significantly improved ( Figure 4 ) and slurry stability ( Figure 5 ).

[0058] The following Table 2 shows the results of the material withholding (2-4.0V) and the change in NaOH alkali content of Examples 1-19 and Comparative Examples 1-8.

[0059] Table 2

[0060] By analyzing the results of Examples 1-19 and Comparative Examples 1-8 of the present invention through Table 1 and Table 2, it can be seen that: (1) Through the scheme provided by the present invention, an O3 layered oxide positive electrode material with Na ion vacancies can be effectively obtained, wherein the concentration of the organic cationic compound solution, the source of the organic cations, the ion exchange temperature, the ion exchange time, the initial Na metal ratio, the selection of the O3 layered oxide positive electrode material, etc. will affect the number of sodium vacancies. For example, high organic cation concentration, long exchange time, high exchange temperature, etc. can significantly increase the Na vacancies. + The probability of exchange will increase, and more sodium vacancies will be generated after sintering. The large size of the organic cation itself and the strong bond strength between the organic cation and the anion will increase the probability of exchange. + The probability of exchange is reduced, and fewer sodium vacancies are ultimately produced. In short, the number of sodium vacancies can be adjusted by adjusting the corresponding parameters, and ultimately the performance of the positive electrode material can be effectively controlled.

[0061] (2) The presence of an appropriate amount of Na ion vacancies improves the electrochemical performance of sodium ion cathode materials with sodium vacancies on the surface to a certain extent, especially when the number of sodium vacancies is between 5-15% of the initial Na metal ratio, which will significantly improve the first efficiency, rate, cycle and other performances. However, if the number of Na ion vacancies accounts for more than 15% of the initial Na metal ratio, the capacity will be easily attenuated rapidly due to excessive loss of active Na; if the number of Na ion vacancies accounts for less than 5% of the initial Na metal ratio, although the capacity loss is reduced, the small amount of sodium vacancies does not significantly change the Na diffusion kinetics, so the other performances are not significantly improved, and the spontaneous Na removal of the cathode material is not significantly alleviated, and the residual alkali content is still very high. In short, appropriate process conditions need to be considered as a whole to achieve the best performance optimization.

[0062] (3) The presence of sodium vacancies significantly improves the air stability. Long-term exposure to air will not have a significant effect on the residual alkali, and the slurry viscosity performance is good. On the one hand, this is related to the effective reduction of free Na in the present invention. On the other hand, due to the increase in sodium vacancies, the oxidation resistance is further improved and the occurrence of spontaneous Na removal is reduced.

[0063] (4) Doping a proper amount of element A into the sodium ion positive electrode material containing sodium vacancies on the surface can further optimize the electrochemical performance of the sodium ion positive electrode material containing sodium vacancies on the surface, so that key performance such as capacity, rate, and cycle are effectively improved. However, due to the different action mechanisms of different doping elements, it is necessary to analyze them in combination with specific situations.

[0064] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium ion positive electrode material having sodium vacancies on the surface, characterized in that: The sodium ion positive electrode material containing sodium vacancies on the surface is an O3 type layered oxide positive electrode material containing sodium vacancies on the surface, and the O3 type layered oxide positive electrode material includes a doping element, and the valence of the doping element in the sodium ion layered oxide is one or more of +1, +2, +3, +4, +5, and +6.

2. The sodium ion positive electrode material having sodium vacancies on the surface according to claim 1, characterized in that: The O3 type layered oxide positive electrode material comprises sheet-shaped and / or block-shaped single crystals with a particle size D50 of 3 μm-10 μm. The sodium vacancies on the surface of the O3 type layered oxide positive electrode material account for 5%-15% of the total sodium content of the O3 type layered oxide.

3. The sodium ion positive electrode material having sodium vacancies on the surface according to claim 1, characterized in that: The composition of the O3 type layered oxide is Na x M y A z O2, wherein 0.7≤x≤1.0, 0<y<1, 0<z<1, M includes at least one element selected from Ni, Fe, Mn, Cu, Zn, and Ti, and the doping element A includes at least one element selected from K, Ca, Mg, Co, Ti, Al, Zr, Ce, Nb, Mo, Sr, Y, Sn, Sb, and W.

4. The sodium ion positive electrode material having sodium vacancies on the surface according to claim 1, characterized in that: The sodium ion positive electrode material slurry with a solid content of 60% and containing sodium vacancies on the surface can still flow normally without gelling after being placed in a 25% humidity environment for 24 hours; the surface residual alkali NaOH content of the sodium ion positive electrode material with sodium vacancies on the surface is 500ppm-1000ppm, and the surface residual alkali NaOH content is 600ppm-1100ppm after being placed in the air for 10 days.

5. The sodium ion positive electrode material having sodium vacancies on the surface according to claim 1, characterized in that: The O3-type layered oxide containing sodium vacancies on the surface has a capacity of more than 135 mAh / g at 0.1C in a 2-4.0V button half-cell at room temperature, an initial efficiency of more than 95%, and a 50-cycle cycle retention rate of more than 95%.

6. A method for preparing a sodium ion positive electrode material having a surface layer containing sodium vacancies according to any one of claims 1 to 5, characterized in that: include: The O3-type layered oxide powder is dispersed in a solution containing an organic cationic compound, stirred under heating conditions, and then filtered, dried and sintered to obtain a sodium ion positive electrode material containing sodium vacancies on the surface.

7. The preparation method according to claim 6, characterized in that: The preparation method of the O3 type layered oxide powder includes a solid phase method and a precursor method, wherein: the solid phase method includes the following steps: after the Na source, M source and A source are uniformly mixed according to a set ratio, sintering at 950°C~1050°C in an air atmosphere for 10h~12h; the precursor method includes the following steps: after the M(OH)2 precursor, Na source and A source are uniformly mixed, sintering at 950°C~1050°C in an air atmosphere for 10h~12h, the Na source includes at least one of sodium carbonate or sodium hydroxide, the M source includes at least one of the oxide, carbonate and hydroxide of the M element, and the A source includes at least one of the oxide, carbonate, phosphate and hydroxide of the A element.

8. The preparation method according to claim 6, characterized in that: The solution containing the organic cationic compound is obtained by dissolving the organic cationic compound in a solvent, wherein: the organic cationic compound comprises one or more of a quaternary ammonium salt and a quaternary phosphonium salt, the quaternary ammonium salt has a general formula of R4NX, the four R groups are independently selected from a C1-C4 alkyl group, and X is Cl - Br - ,I - Any one of the above, wherein the quaternary phosphonium salt has the general formula of R4PX, the four R groups are independently selected from C1-C4 alkyl groups, and X is Cl - Br - ,I - Any one of the above, wherein the solvent includes one or more of deionized water, methanol, ethanol, and propanol.

9. The preparation method according to claim 6, characterized in that: The dispersion temperature is 25℃-75℃, the drying temperature is 50℃-100℃, the drying time is 4h-8h, the sintering temperature is 600℃-800℃, and the sintering time is 6h-8h.

10. A sodium secondary battery, characterized in that The sodium secondary battery comprises the sodium ion positive electrode material having sodium vacancies on the surface as described in any one of claims 1 to 5 or the sodium ion positive electrode material having sodium vacancies on the surface prepared by the preparation method as described in any one of claims 6 to 9.

Citation Information

Patent Citations

  • Lithium-rich manganese-based positive electrode material of lithium ion battery and preparation method of lithium-rich manganese-based positive electrode material

    CN115286042A

  • Positive electrode material, secondary battery and electric equipment

    CN116936795A

  • Sodium-vacancy-containing O3 type layered oxide as well as preparation method and application thereof

    CN117416992A